2017
DOI: 10.1371/journal.pone.0186621
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between video game expertise and fluid intelligence

Abstract: Hundreds of millions of people play intellectually-demanding video games every day. What does individual performance on these games tell us about cognition? Here, we describe two studies that examine the potential link between intelligence and performance in one of the most popular video games genres in the world (Multiplayer Online Battle Arenas: MOBAs). In the first study, we show that performance in the popular MOBA League of Legends’ correlates with fluid intelligence as measured under controlled laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 73 publications
(77 reference statements)
8
56
1
1
Order By: Relevance
“…Rabbit et al [ 8 ] found a modest correlation ( r = .283) between IQ and initial performance in the game “Space Fortress”. Since then, many papers on this topic have been published covering different subjects regarding video games and cognition (for example, see: [ 9 13 ]). In a recent study, the link between gameplay performance in a popular video game called “League of Legends” (LoL) and fluid intelligence was examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbit et al [ 8 ] found a modest correlation ( r = .283) between IQ and initial performance in the game “Space Fortress”. Since then, many papers on this topic have been published covering different subjects regarding video games and cognition (for example, see: [ 9 13 ]). In a recent study, the link between gameplay performance in a popular video game called “League of Legends” (LoL) and fluid intelligence was examined.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the link between gameplay performance in a popular video game called “League of Legends” (LoL) and fluid intelligence was examined. The results showed a correlation between performance on a fluid-intelligence task, the matrix subset from the Wechsler Adult Intelligence Scale–second edition (WAIS-II) and rank in LoL [ 13 ]. Another point of interest within this research field is the question of whether playing video games will enhance cognitive abilities, which seems to yield mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the professional qualification and leadership capabilities of executives in the corporate setting can be fostered by computer games (Marques Filho & Pessôa, 2000, Seriosity, 2007. Indeed, the engagement in videogames has been linked to increases in various types of cognitive abilities, including visual perception and sensorimotor skills, visuospatial thinking, logical-numerical reasoning, problem-solving, decision-making, and general intelligence (Prensky, 2006, Silva, 2008, Rodehffer & Bartlett, 2008, Souza, Silva & Roazzi, 2010, Connolly et al, 2012, Clark, Tanner-Smith, & Killingsworth, 2014, Bediou, 2018, Kokkinakis et al, 2017. Interestingly, such findings are more commonly found in commercial games made solely for the purpose of entertainment rather than those that were developed specifically for educational purposes (Bakar, Inal, & Cagiltay, 2006, Young, Slote, & Cutter, 2012, Clark, Tanner-Smith, & Killingsworth, 2014, perhaps due to economic incentives towards a greater investment in technical quality and to design products that are simultaneously alluring and engaging.…”
Section: The Potential Of Videogamesmentioning
confidence: 99%
“…In addition, the very nature of the interactions and activities that these games offer are those of the requirements for effective adult education and professional qualification according to the specialized literature (Maraschon & Axt, 2005, Santos & Tarouco, 2007, Raupp et al, 2010, Marques Filho & Pessôa, 2000, Seriosity, 2007. Interestingly enough, there is significant evidence of cognitive benefits arising from engagement in videogames, particularly in the context of commercial games made solely for the purposes of entertainment (Prensky, 2006, Silva, 2008, Rodehffer & Bartlett, 2008, Souza, Silva, & Roazzi, 2010, Connolly et al, 2012, Kokkinakis et al, 2017. There also appears to be reason to believe that the positive associations between gaming and cognition, in this order, are of a causal nature (Souza, Silva, & Roazzi, 2010, Bediou, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2018 Colegio Oficial de Psicólogos de Madrid ISSN: 2530-3910 https://doi.org/105093/rpadef2018a15 eventos reglados y organizados (Bányai et al, 2018;Railsback y Caporusso, 2019;Hilvoorde y Pot, 2016;Kari y Karhulahti, 2016;Taylor, 2012), cuestiones que pueden estar relacionadas con la hipótesis bidireccional de la personalidad. En concreto, la práctica regular de los videojuegos y esports estimulan ciertas estructuras cerebrales (Adamos et al, 2017;Hyun et al, 2013;Song, Han y Shim, 2013) y mejoran las capacidades cognitivas como la inteligencia, memoria de trabajo, reflexión, toma de decisiones, flexibilidad cognitiva, búsqueda visual, habilidad multitarea, el aprendizaje procesamiento de la información y el tiempo de reacción, entre otras (Bediou et al, 2018;Bonny y Castaneda, 2017;Chang et al, 2017;Chiappe et al, 2013;Colzato et al, 2012;Deleuze et al, 2017;Kokkinakis et al, 2017;Meinz et al, 2012;Powers et al, 2013;Richard et al, 2018;Sala et al, 2018;Thompson et al, 2014;Walsh et al, 2018); posibilita el desarrollo de habilidades psicológicas como la motivación, concentración, autorregulación, autoconfianza y habilidades sociales, entre otras (Bean et al, 2016;Bertran y Chamarro, 2016;Carbonie et al, 2018;Dindar y Akbulut, 2015;Fuster et al, 2013;Gabbiadini y Greitemeyer, 2017;Lee y Leeson, 2015;Puerta-Cortés et al, 2017); y promueve el desarrollo de valores como el civismo, trabajo en equipo, compromiso, cooperación, comunicación, respeto, cumplimiento de normas, trabajo, autosuperación y disciplina, entre otras (Carbonie et al, 2018;…”
Section: Continuación Tablaunclassified